Metabolite profiling of bioactive compounds in tempe flour and its potential as a hypocholesterolemic functional food - Astawan, Made; Tryas, Anisha Ayuning; Saraswati, Saraswati; Wresdiyati, Tutik; Afifah, Diana Nur; Elda, Frima; Riyanto, Rifqi Ahmad; Putri, Sastia Prama (Frontiers in Nutrition, 2025)
High cholesterol is one of the risk factors for cardiovascular disease, which is currently a global health problem. This study aimed to compare the potential of tempe flour and soybean flour as functional foods for lowering blood lipid levels. This study evaluated both flour’s cholesterol-binding activity and anti-lipase activity in vitro. In addition, metabolomic profiling using GC-MS was conducted to identify bioactive compounds contributing to the hypolipidemic effect. The results showed that compared to soybean flour, tempe flour had a higher cholesterol-binding activity (27.66 vs. 14.98%, p < 0.05) and stronger anti-lipase activity (23.24 vs. 15.03%, p < 0.05). GC-MS analysis revealed that tempe flour was rich in isoflavones, amino acids, organic acids, meglutol, and GABA. These components are suspected to contribute to the hypolipidemic effect through mechanisms of inhibiting cholesterol synthesis, forming cholesterol esters, and increasing the excretion of cholesterol and bile acids. These findings suggest that tempe flour has greater potential as a functional food for preventing and managing dyslipidemia.